2017
DOI: 10.1093/dnares/dsw061
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide analysis of cis-regulatory element structure and discovery of motif-driven gene co-expression networks in grapevine

Abstract: Coordinated transcriptional and metabolic reprogramming ensures a plant’s continued growth and survival under adverse environmental conditions. Transcription factors (TFs) act to modulate gene expression through complex cis-regulatory element (CRE) interactions. Genome-wide analysis of known plant CREs was performed for all currently predicted protein-coding gene promoters in grapevine (Vitis vinifera L.). Many CREs such as abscisic acid (ABA)-responsive, drought-responsive, auxin-responsive, and evening eleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 95 publications
(216 reference statements)
2
33
0
Order By: Relevance
“…Because motif composition is also an important indicator to classify different genes, we then analyzed and compared the motif composition of the SBP protein sequences [49,78,79]. Corresponding to the results of conserved domain analysis, the distribution of Motifs 1 and 2 were highly conserved in all sequences, and the annotation showed that they were all zinc-binding sites (Figure 13).…”
Section: Discussionmentioning
confidence: 99%
“…Because motif composition is also an important indicator to classify different genes, we then analyzed and compared the motif composition of the SBP protein sequences [49,78,79]. Corresponding to the results of conserved domain analysis, the distribution of Motifs 1 and 2 were highly conserved in all sequences, and the annotation showed that they were all zinc-binding sites (Figure 13).…”
Section: Discussionmentioning
confidence: 99%
“…We next tested whether the AP2/ERF cis ‐regulatory elements (CREs) (GCC‐box and DRE/CRT) exhibited canonical CRE properties (Wong et al ., ). Indeed, the GCC‐box was highly enriched ( P < 1.00E‐05) in the promoters of Vv‐m (70 genes, P < 1.17E‐09) and Vv‐r (64 genes, P < 2.97E‐07) GCN genes (Figure d; Table S9).…”
Section: Resultsmentioning
confidence: 97%
“…The default output of atted‐ii (top 300 co‐expressed genes ranked by MR value) from the At‐m and At‐r GCN was further shortlisted and analyzed. Shortlisted co‐expressed genes in grapevine and A. thaliana GCNs were tested for over‐representation using MapMan BIN functional categories (Lohse et al ., ) and Fisher's exact test, and an FDR correction was applied using the appropriate species background, as previously described (Wong et al ., ). Significantly enriched BIN categories were defined as categories having an FDR of <0.05.…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…These results suggest that VlbZIP30 is likely to enhance A. thaliana drought tolerance by regulating downstream genes containing a perfect G-box (CACGTG). Large-scale transcriptome analyses also show that the G-box (CACGTG) was highly enriched in stress-responsive genes in grapevines (Wong et al. , 2017).…”
Section: Discussionmentioning
confidence: 99%